Analisis Hukum Islam terhadap Pandangan Masyarakat Desa Sidomojo Krian Sidoarjo tentang Pinjaman pada Bank Titil dan Rentenir - Rizki Khoirunnisa (Maliyah : Jurnal Hukum Bisnis Islam, 2019)
This article discusses the analysis of Islamic law on the views of the Muslim community in the village of Sidomojo Krian Sidoarjo regarding loans through moneylenders and credit banks. This research is field research in the town of Sidomojo Krian Sidoarjo and is qualitative. The data collection techniques used were interviews and observations, then analyzed using descriptive analysis methods. From the results of the study, it is known that three loan shark customers and three titil bank customers agree that the law of bank interest is haram because it is the same as usury. However, they still borrow from these two places because of economic needs, and the process of borrowing from these places is more straightforward. The opinion of those who forbid bank interest is following Islamic law. In contrast, their actions of borrowing through moneylenders and bank credit are allowed as long as they are forced to do so as a rule "The condition of dharurah will allow something that was originally prohibited." If the compulsion is lost, then the law returns to its origin, which is haram. Seeing that their economy is not improving after making loans through moneylenders and bank-titil, then they should no longer make loans in these two places or in other areas that apply interest.